Enlarged brick blocks as an alternative to masonry - Prusakova Maria; Mkrtchyan Armen; Pugach Evgeniy (E3S Web of Conferences, 2020)
Brick structures are one of the most common and useful construction materials. However, brick laying consists of the most labor-intensive processes with the largest part of manual works. The main purpose of the research is to find an alternative technology for the brick structures construction that have geometric and physical parameters of brickwork, the processes of which are less labor-intensive and more mechanized. Using factory-made enlarged brick blocks was suggested in the article as an alternative. A brick block is a factory - made element of a brick wall structure that is installed in the design position by crane equipment. By reducing the part of manual labor in installing the brick block, the total duration of construction is reduced while maintaining the final result – a brick wall. The research method was a comparative analysis of the resulting indicators of construction of structures made of individual bricks and installation of enlarged brick blocks. As a model for comparative analysis, a brick wall of specified parameters was proposed, on the basis of which calculations were made. The results show diagrams of labor and material resources spent on the construction of the wall for the two technologies under consideration. Based on the results obtained, we can conclude that it is possible to use enlarged brick blocks of high factory readiness as an alternative to masonry.